(untitled) (Kohesi: Jurnal Sains dan Teknologi, 2025)
The Objective of this study is to evaluate students’ preferences toward three common educational methods in universities: online, offline, and hybrid learning. This research employs a quantitative approach and utilizes a survey method to collect data from students across various academic programs. The gathered data were analyzed using descriptive and inferential statistics to identify preference trends and the factors influencing students’ choices. The findings indicate that the hybrid learning method is favored by the majority of students due to its flexibility and ability to accommodate diverse learning needs. While some students still prefer offline learning because of the necessity for direct interaction in the learning process, online learning remains preferred for its accessibility. These results carry significant implications for higher education policy development, as they contribute to the creation of a more flexible and efficient learning system.